Entomological Index and Home Environment Contribution to Dengue Hemorrhagic Fever in Mataram City, Indonesia - Satoto, Tri Baskoro Tunggul; Pascawati, Nur Alvira; Wibawa, Tri; Frutos, Roger; Maguin, Sylvie; Mulyawan, I Kadek; Wardana, Ali (Kesmas, 2020)
Indonesia is a member of Southeast Asia Regional Office (SEARO) ranked the first in dengue hemorrhagic fever (DHF) problem based on incidence rate (IR) and case fatality rate (CFR). Several provinces in Indonesia experience an outbreak, one of which is the Mataram City in West Nusa Tenggara Province. Mataram City is an endemic area of DHF because the DHF cases are always found in three consecutive years with the number of cases that fluctuate and tend to increase. This study aimed to obtain factors that could be used to improve early warning systems in controlling DHF. This study used a case control design with a ratio of 1:1 to 180 house holds. The results showed that home environmental factors, such as no ceiling, indoor and outdoor temperature that had the potential for breeding places for mosquitoes, no wire net in ventilation, low lighting and high humidity, related to DHF transmission. Vector distibution with entomology index showed that the existence of larvae, eggs and mosquitoes played a role in dengue transmission. The dominant factors affecting the transmission of dengue in Mataram City are the condition of the ceiling and the existence of mosquito eggs in the house.